Defining Shugendō critical studies on Japanese mountain religion - Castiglioni, Andrea; Rambelli, Fabio 1963-; Roth, Carina 1971- (Bloomsbury Academic, 2020)
"Defining Shugendo brings together leading international experts on Japanese mountain asceticism to discuss what has been an essential component of Japanese religions for more than a thousand years. Contributors explore how mountains have been abodes of deities, a resting place for the dead, sources of natural bounty and calamities, places of religious activities, and a vast repository of symbols. The book shows that many peoples have chosen them as sites for ascetic practices, claiming the potential to attain supernatural powers there. This book discusses the history of scholarship on Shugendo, the development process of mountain worship, and the religious and philosophical features of devotion at specific sacred mountains. Moreover, it reveals the rich material and visual culture associated with Shugendo, from statues and steles, to talismans and written oaths."